2018
DOI: 10.1007/s00424-018-2224-y
|View full text |Cite
|
Sign up to set email alerts
|

Coronary arterial vasculature in the pathophysiology of hypertrophic cardiomyopathy

Abstract: Alterations in the coronary vascular system are likely associated with a mismatch between energy demand and energy supply and critical in triggering the cascade of events that leads to symptomatic hypertrophic cardiomyopathy. Targeting the early events, particularly vascular remodeling, may be a key approach to developing effective treatments. Improvement in our understanding of hypertrophic cardiomyopathy began with the results of early biophysical studies, proceeded to genetic analyses pinpointing the mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 145 publications
(169 reference statements)
2
10
0
Order By: Relevance
“…Similar to our analysis results, the differentially expressed genes are also related to epidermis development in the dilated cardiomyopathy (37). In addition, the mechanism of metabolism has an important in uence on the pathophysiological process of HCM (38). Studies have shown that the decrease of left ventricular systolic function in female HCM mice is related to the decrease of activities of fatty acid transporter (CD 36) and AMP activated protein kinase (AMPK) (39).…”
Section: Discussionsupporting
confidence: 76%
“…Similar to our analysis results, the differentially expressed genes are also related to epidermis development in the dilated cardiomyopathy (37). In addition, the mechanism of metabolism has an important in uence on the pathophysiological process of HCM (38). Studies have shown that the decrease of left ventricular systolic function in female HCM mice is related to the decrease of activities of fatty acid transporter (CD 36) and AMP activated protein kinase (AMPK) (39).…”
Section: Discussionsupporting
confidence: 76%
“…Various histological studies have demonstrated subendocardial arterioles in HCM patients to have smaller cross-sectional lumen area 29 and greater coronary flow resistance 30 than controls, and authors have speculated whether this could be due to compressive effects of regional hypertrophy. 31,32 This hypothesis is supported by our finding of an inverse correlation between subendocardial MD and MPR, however histological corroboration of this is still lacking. The incremental increase in MD in segments with hypertrophy and scarring in our cohort correlates with an increase in ECV and LGE; and would seem to be more attributable to a gradual interstitial fibrotic process that ensues in these segments, as other authors have observed.…”
Section: Discussionmentioning
confidence: 76%
“…Functional studies have reinforced this concept as impaired myocardial blood flow measured with PET has been found in areas with delayed gadolinium enhancement at MRI, generally associated with myocardial scarring [5]. Interestingly, early microvascular abnormalities and dysfunction in HCM have been found to precede myocardial alterations such as myocyte hypertrophy [14]. Long-term, intramural coronary dysfunction has been identified as a predictor of LV remodeling (including the end-stage phase), characterized by extensive progression of replacement fibrosis, as well as heart failurerelated outcome [6,7].…”
Section: Discussionmentioning
confidence: 99%